A study of laser melt injection of TiN particles to repair maraging tool steels1. (30th January 2014) - Cabeza, M.; Castro, G.; Merino, P.; Pena, G.; Roman, M.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The tools and dies surface may suffer from severe damage in service due to sharp working conditions, such as extreme thermomechanical loading and abrasive environments. The steel and high strength alloys used for these tools are usually very expensive; hence, those in charge of surface repairing should welcome laser processes in order to increase the service life of the tool and shorten the time required to amortize the investment made. In this paper, a high power laser has been used to modify the microstructure as well as the surface properties of low nickel (14 wt.%) maraging steel by means of the laser melt injection process. The power of TiN was injected into the laser‐melted steel. The microstructure, hardness and wear resistance of the metal matrix composite 'new surface', followed by peak‐age hardening, have been studied. Laser parameters were optimized to obtain a defect‐free material. Laser surface processing impairs the surface properties of the maraging steel as hardness decreases in the heated regions; thus, a final age hardening treatment is necessary to obtain the required high strength typical of maraging steels. Copyright © 2014 John Wiley & Sons, Ltd.